Conventionality control and Amendment 95/2016: a Brazilian case of unconstitutional constitutional amendment - Roznai, Yaniv; Camargo Kreuz, Letícia Regina (Revista de Investigações Constitucionais, 2018)
This article presents reflections on Brazilian Constitutional Amendment 95/2016, which established the New Tax Regime and consequently the ceiling of public spending in Brazil for a period of twenty years, which has serious consequences for Brazilian public services. The hypothesis defended in the study is that Amendment 95/2016 is an unconstitutional constitutional amendment, since it violates the essence of the Social State present in the original text of the 1988 Constitution and has direct influences on the guarantee of fundamental rights, which constitute stone clauses (cláusulas pétreas). Thus, the study starts with the technical analysis of the Amendment. Next, the concept and content of the stone clauses in the Brazilian constitution are analyzed to propose the possibility of conventionality control as an alternative, focusing on the Intermerican Convention on Human Rights, UN Convention on the Rights of Persons with Disabilities and International Covenant on Economic, Social and Cultural Rights. It is concluded that conventionality control of the Amendment is imperative. The methodology used is the bibliographic analysis on the themes, as well as the projection of data on the economic and social effects of Amendment 95/2016.